Effects of the origin of potato planting material on morphological characteristics of seed tubers - Poštić Dobrivoj; Momirović Nebojša; Broćić Zoran; Stanisavljević Rade; Štrbanović Ratibor; Đokić Dragoslav; Jovović Zoran (Journal on Processing and Energy in Agriculture, 2016)
The effects of the origin of planting material on the mophological characteristics of seed tubers of the Kondor potato cultivar (Solanum tuberosum L.) were investigated within a two-year study (2009-2010). The production conditions of potato planting material at lower altitudes (700 m.a.s.l.) contributed to producing seed tubers of greater physiological age, resulting consequently in a significantly lower average length of sprouts per tuber 1.38 mm, or 13.49 % less, in comparison with the length of sprouts per tuber determined in tubers originating from 1300 m.a.s.l. Using the Kondor potato cultivar originating from 700 m.a.s.l. as a planting material (which forms a larger number of sprouts per tuber), a higher number of primary stems per plant could be expected, which would be beneficial to seed production (a greater number of small tubers). Provided the Kondor potato cultivar originating from 1300 m.a.s.l. is used as a planting material (which forms a smaller number of sprouts per tuber and potentially a smaller number of stems per plant), the seed tubers should be used in early potato production and for commercial purposes (a small number of large tubers).